O voto dissidente, um caso de variação no registro da sentença judicial: uma abordagem estratégica - Menéndez, Salvio Martín (2025)
The general objective of this interdisciplinary work between law and linguistics is to strategically analyze the discursive construction of the dissenting opinion based on the analysis of this type of discourse in the Inter-American Court of Human Rights. First, we will describe the judicial practice of issuing dissenting opinions from a legal perspective, and second, we will analyze the discursive strategies (Menéndez, 2019) used by judges, as discursive subjects, to express and justify a point of view contrary to that of most of their colleagues. Our approach is the strategic analysis of the combination of lexico-grammatical, pragmatic, and rhetorical resources, which are inscribed as a case of variation within the register we call judicial ruling (Menéndez & Vázquez Neira, in press). Ultimately, we aim to demonstrate how dissent functions discursively. We will illustrate our analysis through a discursive series (Menéndez, 1997) composed of 32 dissenting opinions issued by the Inter-American Court of Human Rights in 2021. The conclusions aim to demonstrate the effectiveness of strategic analysis in general, based on a specific series within a specific discursive genre: the legal one.